2021
DOI: 10.3390/app112411941
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration by Dedifferentiated Fat Cells Using Composite Sponge of Alfa-Tricalcium Phosphate and Gelatin in a Rat Calvarial Defect Model

Abstract: Mechanical and resorbable scaffolds are in high demand for stem cell-based regenerative medicine, to treat refractory bone defects in craniofacial abnormalities and injuries. Multipotent progenitor cells, such as dedifferentiated fat (DFAT) cells, are prospective sources for regenerative therapies. Herein, we aimed to demonstrate that a composite gelatin sponge (α-TCP/GS) of alfa-tricalcium phosphate (α-TCP) mixed with gelatin scaffolds (GS), with/without DFATs, induced bone regeneration in a rat calvarial def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…To evaluate the potential of bone regeneration, two types of PCL-based scaffolds (PCL and HAp-PCL) were implanted into the critical-sized calvaria bone defect in F344 rats, as previously used [ 34 , 35 ]. In this study, a negative control group (no implantation) was omitted because little bone formation without any implantation was previously confirmed, and the effect of hydroxyapatite coating on the bone formation efficacy by PCL porous scaffold was focused.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the potential of bone regeneration, two types of PCL-based scaffolds (PCL and HAp-PCL) were implanted into the critical-sized calvaria bone defect in F344 rats, as previously used [ 34 , 35 ]. In this study, a negative control group (no implantation) was omitted because little bone formation without any implantation was previously confirmed, and the effect of hydroxyapatite coating on the bone formation efficacy by PCL porous scaffold was focused.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to distinguish between DFAT cells and AD-MSCs when referring to adipose stem cells, as AD-MSCs are adult stem cells while DFAT cells are a form of induced pluripotent stem cells. Studies to compare DFAT cells and AD-MSCs for bone regeneration showed that both DFAT cells and AD-MSCs demonstrated mesenchymal stem cell characteristics and both have similar osteogenic potentials [ 71 , 72 ], and DFAT cells have been proven to be effective for bone regeneration in a rat calvarial model [ 73 , 74 ]. Despite showing positive scientific outcomes and offering great promises, DFAT cells are still not as widely used as AD-MSCs due to a number of obstacles and challenges such as cell culture purity, phenotypic properties, and dedifferentiation mechanisms [ 75 ].…”
Section: From Fat To Bone: Achieving Bone Regeneration With Ad-mscsmentioning
confidence: 99%
“…Gelatin, a macromolecular hydrocolloid with high surface activity and viscosity, typically does not require the addition of surfactants to achieve low surface tension in its concentrated solutions [79]. In addition, gelatin has natural holes that can hold cells [80]. However, both have poor mechanical and osteoconductive properties, making it challenging to use them alone as a component of a scaffold for bone tissue synthesis.…”
Section: Chitosan and Gelatinementioning
confidence: 99%
“…Endothelial cells (ECs) and supporting cells can be co-cultured to generate prevascular material that can fuse with the host vasculature and enhance perfusion after implantation. With the ability to self-renew and immunosuppress, MSCs with multipotential and homing properties are excellent candidates for cell therapy and enhance angiogenesis by increasing the expression of angiogenesis-related factors [28,80,130,131]. Within one week of implantation, the PSC-EC network survives, which was generated from endothelial cells (ECs) derived from human induced pluripotent stem cells (iPSCs), anastomoses to the host vasculature, and continues to function for eight weeks after implantation.…”
Section: Co-culturementioning
confidence: 99%